The Effect of Piroxicam Administration before Surgical Removal of Mandibular Mesioangular Third Molar Compared with Acetaminophen. - Refoua Y; Mahdavi O (Tehran University of Medical Sciences, 2000)
: 32 patients were entered in randomized double blind clinical research. The patients were"ndivided into two groups. Group A(18 patients) were given a single dose of 20 mg Piroxicam one hour"npre-surgery. Group B(14 patients) were received 325 mg Acetaminophen every six hours immediately"nafter surgery. The mouth opening was measured pre-surgical treatment. Pain relief was evaluated in both"ngroups lsl and 8th hour after surgery. The mouth opening was measured lsl and 7,b day after surgery. The"nresults showed that the analgesic effects of Piroxicam were higher than acetaminophen, however, the"ncomparison of trismus means revealed no significant difference.